Analysis of Students’ Collaboration Skills through Project-Based Learning Model - Jeliana Veronika Sirait; Erlida Amnie (Universitas Sultan Ageng Tirtayasa, 2023)
Student collaboration can be trained by implementing a project-based learning (PjBL) model because this model has great potential to produce a meaningful learning for students and can be a provision for them to face the future when they enter the world of work. This research aimed to obtain the level of students’ collaboration skill so that it can be used as a reference material to explore the potential of students. The type of this study is descriptive using a quantitative approach. The instrument used is an observation sheet to observe student collaboration skills during learning by applying PjBL to Fluid material which consists of 5 indicators and 10 descriptors. Data analysis uses the average percentage of students’ collaboration skills indicators. The average percentage of collaboration skills indicators is 76.33%. Collaboration skills possessed by students during learning by applying the PjBL model are classified as collaborative in accordance with the assessment criteria reference. So it is concluded that to foster student collaboration skills, students can apply the PjBL model in physics learning activities.